PENGARUH EPS, PER DAN PBV TERHADAP HARGA SAHAM (PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR JII) - Permatasari, Ninda Putri; Isharijadi, Isharijadi; Wihartanti, Liana Vivin (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2020)
The purpose of this study was to determine the effect of EPS, PER and PBV on stock prices. The research sample is 8 manufacturing sector companies registered in the Jakarta Islamic Index in 2016-2018. The type of data is quantitative descriptive using a purposive sampling method for sampling. The data analysis technique to test the hypothesis is multiple linear analysis. The results of the study show that EPS and PBV have a significant positive effect on stock prices, PER has a significant negative effect on stock prices. Because, when analyzing there are several company stock prices rising and profits falling a share. The three EPS, PER and PBV variables have an effect on the stock price simultaneously.